(untitled) (Bangladesh Journal of Medical Science, 2021)
Ectopic salivary gland tissue (ESGT) is salivary tissue located outside the major, minorand accessory salivary glands. Neoplasms rarely arise from ESGT, let alone carcinoma expleomorphicadenoma (CEPA) which is a malignant tumour that arises from the epithelialcomponent of pleomorphic adenoma. It usually occurs in the parotid gland and in lesserinstances, from submandibular gland or minor salivary glands. Herein, we report a rare caseof CEPA in right supraclavicular ESGT of a 67-year-old lady.She underwent complete surgicalexcision of the mass and is free from any recurrence to date. Brief review of pathogenesis,clinical features and treatment of ectopic CEPA are discussed. A thorough review of the Englishliterature reveals that our patient may be the second case of ectopic CEPA in the neck regionever reported to date. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.190-193